Synthesis of 2-hydroxybenzaldehyde derivatives as anti-cancer agent (prostate cancer) using pharmacophore modelling and in vitro brine shrimp assay as preliminary identification of cytotoxic properties - Siti Sakinah, Binti Ilias (Universiti Malaysia Sarawak, UNIMAS, 2012)
Cancer is the number one killer disease which affected human population nowadays. This disease characterized by uncontrolled cell proliferation. It can be detected through medical check up such as screening test or medical imaging. Prostate cancer tends to attack men mostly in around 50 years old. Prostate cancer is related to male reproductive system especially the prostate gland. The spreading of the tumors starts from the prostate glands. In this research, a new method was develop to design a new anti-cancer agent to prevent the uncontrolled activity of the cancer cells based on Computer Aided Drug Design (CADD) studies. Thus, twenty of 2-hydroxybenzaldehyde derivatives have been synthesized via Schiff base condensation reaction using 2-hydroxybenzaldehyde as a starting material. All 2- hydroxybenzaldehyde derivatives were characterized by Thin Layer Chromatography (TLC), melting point, FT-IR, GC-MS, 1H NMR and elemental analysis and cytotoxicity test against Artemia salina was performed. These ligands were virtually validated for the pharmacophore modelling in order to search potential anti-cancer agents by using of LigandScout 3.03 software package. Seven established anti-cancer agents from published literature and database were selected as a training set and generated the pharmacophore hypothesis or model. The best pharmacophore hypothesis or model consists of Hydrogen Bond Acceptor (HBA) and Hydrophobic (HY). This feature was then validated with the test set consists of the 20 synthesized ligands by mapping to the pharmacophore model. The tests set with higher fitting values were then selected to predict the activity of anti-cancer activity by cytotoxicity assay. This cytotoxicity test determined which ligand shows the strongest activity as anti-cancer agent. Out of 20 compound of the test set, 14 shows significant mapping mode with the best hypothesis model. Thus, these compounds have the higher potential as anti-cancer agent.